دور النسب المالية في تقويم أداء المشروع الاقتصادي دراسة تطبيقية على الشركة العربية السورية للصناعات الإلكترونية (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف هذا البحث إلى التعريف بالنسب المالية كواحد من أهم أساليب التحليل المالي المستخدمة في دراسة المركز المالي للمشروع, والحكم على نتائج أعماله. ويقوم هذا الأسلوب على أساس أن فحص أي رقم من أرقام القوائم المالية لا يدل في حد ذاته على شيء مهم, ولا يقدم معلومات مفيدة, ولكن تظهر أهمية هذا الرقم إذا قورن بغيره من الأرقام, أو نسب إليها. وتهدف النسب المالية إلى تقديم مجموعة من المعلومات والمؤشرات تستند إليها إدارة المشروع في عمليات التخطيط والرقابة واتخاذ القرار, وذلك من خلال تقويم أداء هذا المشروع, وكشف انحرافاته, والتنبؤ بالمستقبل. لذلك فإن النسب المالية لا تقدم أحكاماً قطعية حول حالة المشروع قيد الدراسة والتحليل, وإنما تساعد في اتخاذ القرارات الرشيدة التي تمكن هذا المشروع من إتمام عملياته المخطط لها بنجاح. This research identifies the financial ratios as one of the most important financial analysis techniques used in the study of the financial position of the project and judgment of the results of its operations. This technique indicates that examining any figure from the financial statements does not point to something important, nor does it present useful information. However, the importance of this technique becomes apparent if compared with, or related to other figures. The purpose of financial ratios is to provide a set of information and indexes on which the project management depends in the processes of planning, control, and decision making through evaluating the performance of the project, detecting its deviations, and forecasting its future. Therefore, financial ratios do not provide definitive judgment as regards the condition of the project- under study and analysis; rather, it helps in making prudent decisions that enable this project to accomplish its planned operations successfully.